ANALISIS PEMBIAYAAN PENANGGULANGAN GIZI BURUK PADA BALITA DI KABUPATEN LOMBOK TENGAH PROVINSI NUSA TENGGARA BARAT - Irna Agustina; Toto Sudargo; Diah Ayu Puspandari (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2021)
Background: According to WHO more than 50% of infant andchild mortality is related to malnutrition, a nutritional problemthat needs to be solved quickly and appropriately. Based on theresults of PSG Kadarzi years 2012-2015 the prevalence ofemaciation according to indices of BB /TB or BB/PB was 7,43%,7,32%, 9,81%, and 7,6%. Those number fluctuate but if thisnutritional problem is ignored it will cause problems ofdevelopment in the future. Consider this phenomenon we canfind out how the financing of prevention of malnutrition in CentralLombok regency issued by government and society.Objective: Identify financing countermeasures of malnutritionamong children under five years old in the district of  Central Lombok, West Nusa Tenggara (NTB)Methods: This research is a descriptive study and crosssectionalresearch design with quantitative dates. This researchwas conducted in Central Lombok regency, West NusaTenggara Province. The subjects of this study were the motheror malnourished children keeper as many as 30 people. Thedata analysis was conducted by descriptive the financingcountermeasures of malnutrition in Central Lombok regency.Results: From the search results and interviews it showed thatthe malnutrition countermeasures costs spent by thegovernment was IDR2.816.913,00/person/year and the amountof public expenses was IDR7.874.100,00/person/year. Thelarge proportion of the cost of government was 26,35% and bythe public was 73,65%.Conclusion: The society expenses were 2,79 times as high asgovernment expenses on malnutrition countermeasures onchildren under five in Central Lombok regency.